Paranasal Sinus Mucoceles: Report of Cases in Four Different Locali-sations, Two of Which are Uncommon - Akıdıl, Ayse Oznur; Yılmaz, Mahmut Sinan; Guven, Mehmet (Fırat University, 2012)
Paranasal sinus mucoceles are relatively common, benign, slow growing cystic lesions filled with mucous or mucopurulent material that overfill the sinus. They are locally expansile and can cause bone destruction. These lesions are thought to be secondary to an obstruction of the sinus ostium caused by an inflammation, trauma, fibrosis, or previous surgery. They are frequently located in the frontal sinus and ethmoid sinuses, and are seen rarely in the maxillary and sphenoid sinuses. Middle turbinate and septum mucoceles are seen very rarely. In this report we present a literature review and five cases of paranasal sinus mucocele in four different localisations, two of which are uncommon.

Paranazal sinüs mukoselleri göreceli olarak yaygın görülen, sinüsü dolduran ve içi mukus veya mukopürülan materyal ile dolu, sinüsü dolduran, lokal olarak genişleyen ve kemik harabiyetine sebep olabilen, benign, yavaş büyüyen kistik lezyonlardır. Bu lezyonların bir inflamasyon, travma, fibrozis veya geçirilmiş cerrahiye bağlı olarak ortaya çıkan sinüs ostiumunun tıkanması sonucu olduğu düşünülmektedir. En sık yerleşim yeri frontal sinüs ve etmoit sinüslerdir. Maksiller ve sfenoid sinüslerde nadiren görülürler. Orta konka ve septum mukoselleri nadiren görülmektedir. Bu yazıda biz, iki tanesi alışılmadık olmak üzere dört ayrı lokalizasyonda yerleşmiş beş paranazal sinüs mukoseli vakasını sunuyor ve literatürü gözden geçiriyoruz.
Paranazal Sinüs Mukoselleri : İkisi Nadir Dört Farklı Lokalizasyonda Vaka Sunumu